Do parents and adolescents talk about reproductive health? Myanmar adolescents' perspective - Oo, Yin Thet Nu; Zaw, Ko Ko; Than, Kyu Kyu; Mg, The Mg; Mar, Kyi Kyi; Aye, San San (South East Asia Journal of Public Health, 2013)
Adolescence is a transitional period and an important stage in an individual's life. Adolescents are at risk of adverse reproductive health outcomes such as unplanned or unwanted pregnancy, unsafe abortions, maternal health complications, and sexually transmitted diseases (STDs) including HIV/AIDS. Previous studies indicate that adolescents whose parents talk to them about sex tend to be less sexually active and more likely to use an effective means of contraception. The objective of the study was to find out the level and content of communication between adolescents and their parents. Ease of communication, future intentions to discuss with parents and confidence in parents' knowledge of reproductive health were also examined. A cross sectional descriptive study using structured questionnaire was conducted among 91 adolescents (11-19 years old) in North Okkalapa Township of Yangon Division, Myanmar. The majority of the people there had little knowledge on pubertal changes and STDs, and moderate knowledge on contraception. Sixty three percent of adolescents communicated at least once with their parents on reproductive health within the last 6 months: 6.8% with fathers and 62.6% with mothers. Only 15.4% talked more than three times. Girls were more likely to communicate with mothers than boys (79% vs. 33%, P<0.001). The main topic of discussion among mother and girls is menstruation, and among mothers and boys, HIV/AIDS/STDs are mainly discussed. Regarding the ease of communication, only 15% felt comfortable talking with parents. Most of the adolescents (89%) had positive attitude towards communicating with their parents. The findings suggest the need to involve parents in existing adolescent reproductive health programs and design interventions focusing on parents to promote parent-adolescent communication. DOI: http://dx.doi.org/10.3329/seajph.v1i1.13219 South East Asia Journal of Public Health 2011:1:40-45